The Wound-Healing Potential of Olea europaea L. Cv. Arbequina Leaves Extract: An Integrated In Vitro, In Silico, and In Vivo Investigation - Tarfah Al-Warhi; Abeer H. Elmaidomy; Sherif A. Maher; Dalia H. Abu-Baih; Samy Selim; Mha Albqmi; Mohammad M. Al-Sanea; Taghreed S. Alnusaire; Mohammed M. Ghoneim; Ehab M. Mostafa; Shaimaa Hussein; Ashraf K. El-Damasy; et al. (Metabolites, 2022)
Olea europaea L. Cv. Arbequina (OEA) (Oleaceae) is an olive variety species that has received little attention. Besides our previous work for the chemical profiling of OEA leaves using LC–HRESIMS, an additional 23 compounds are identified. An excision wound model is used to measure wound healing action. Wounds are provided with OEA (2% w/v) or MEBO® cream (marketed treatment). The wound closure rate related to vehicle-treated wounds is significantly increased by OEA. Comparing to vehicle wound tissues, significant levels of TGF-β in OEA and MEBO® (p < 0.05) are displayed by gene expression patterns, with the most significant levels in OEA-treated wounds. Proinflammatory TNF-α and IL-1β levels are substantially reduced in OEA-treated wounds. The capability of several lignan-related compounds to interact with MMP-1 is revealed by extensive in silico investigation of the major OEA compounds (i.e., inverse docking, molecular dynamics simulation, and ΔG calculation), and their role in the wound-healing process is also characterized. The potential of OEA as a potent MMP-1 inhibitor is shown in subsequent in vitro testing (IC50 = 88.0 ± 0.1 nM). In conclusion, OEA is introduced as an interesting therapeutic candidate that can effectively manage wound healing because of its anti-inflammatory and antioxidant properties.